2021
DOI: 10.1186/s13052-021-01011-w
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors of retinopathy of prematurity in an Italian cohort of preterm infants

Abstract: Objective Non-negligible differences in retinopathy of prematurity (ROP) and its risk factors between different neonatal intensive care units (NICUs) are reported. Our aim was to assess the incidence and risk factors for ROP development in a large cohort of very preterm infants who were assisted in two Italian NICUs. Methods Preterm infants with gestational age between 23+ 0 and 29+ 6 weeks were stratified into subgroups of infants who developed RO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 38 publications
0
19
0
2
Order By: Relevance
“…Of 1,347 potentially relevant studies identified from the initial search after removing duplicates, 1,123 records were excluded after title and abstract screening. 222 full-text records were examined for eligibility and additional 5 records were identified from other sources (Dammann et al, 2009;Liu et al, 2012;Güran et al, 2013;Bas et al, 2018;Dani et al, 2021). Following detailed evaluation, 63 records were included for meta-analysis.…”
Section: Search Results and Description Of Studiesmentioning
confidence: 99%
“…Of 1,347 potentially relevant studies identified from the initial search after removing duplicates, 1,123 records were excluded after title and abstract screening. 222 full-text records were examined for eligibility and additional 5 records were identified from other sources (Dammann et al, 2009;Liu et al, 2012;Güran et al, 2013;Bas et al, 2018;Dani et al, 2021). Following detailed evaluation, 63 records were included for meta-analysis.…”
Section: Search Results and Description Of Studiesmentioning
confidence: 99%
“…Obteve-se como correlação estatística significativa para o desenvolvimento da ROP, neste estudo, o uso de cateteres, incluindo-se o PICC, o que difere de outros estudos (9)(10) que reportam fatores de risco associados ao surgimento do problema, sendo um aspecto a ser investigado em outras coortes futuramente, pois o uso de cateteres venosos..centrais..e..mesmo..umbilicais..é..prática largamente adotada nas UTINs. Até o momento, estudos têm evidenciado taxas de complicações entre os cateteres venoso central umbilical e periféricos em recém-nascidos, (19)(20) entretanto, sem correlação com a ROP especificamente, conforme ficou demonstrado em nossos achados.…”
Section: Discussionunclassified
“…(7)(8) Encontram-se descritos como fatores de risco para o desenvolvimento da ROP: Apgar menor que 7, flutuação nos níveis de oxigênio nas primeiras semanas de vida, uso de oxigenioterapia, necessidade de ventilação mecânica, transfusão sanguínea, persistência do canal arterial, baixo peso da criança para a IG, asfixia perinatal, gestação múltipla, sepse e meningite. (7,(9)(10) Tem impacto na qualidade da visão ao longo da vida, podendo evoluir para cegueira, por isso a importância de a enfermagem, cuja maioria de cuidadores dos RNPT hospitalizados encontra-se nessa categoria profissional, estudá-la, preveni-la e tentar minimizar suas consequências o mais precocemente possível. Para que isso seja possível, recomenda-se conhecer esse fenômeno nas distintas realidades de cuidado em saúde aos RNPT.…”
Section: Abstract Introduçãounclassified
“…In a more contemporary cohort, we have previously shown that those infants with no ROP had a higher intake of MOM (mL · kg −1 · day −1 ) compared with infants with any ROP ( 20 ). Dani et al ( 28 ) recently presented that increasing MOM intake reduced the risk of ROP development in an Italian cohort of very preterm infants. In our cohort, however, the proportional intake of PN seemed to attenuate the relationship observed between MOM and severe ROP.…”
Section: Discussionmentioning
confidence: 99%